Relevansi Teori, Ideologi Dan Teologi Dalam Filsafat Ekonomi Islam - Ajeung Syilva Syara Noor Silmi Sudrajat; Ai Reni Ratnasari1 (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2023)
The relationship between theory, ideology and theology in Islamic economic philosophy creates a strong foundation for building an economic system based on Islamic values. This creates hope for achieving a balance between economic growth and social justice. This journal examines the complex relationship between theory, ideology and theology in the context of Islamic economic philosophy. Islamic economic philosophy is a scientific discipline that combines economic principles with the teachings of the Islamic religion. In this research, the author uses a historical approach, a comparative or comparison approach and the researcher also uses a conceptual approach. This is done to dig deeper into the relationship between theory, ideology and theology of Islamic economic philosophy. This paper seeks to explain how Islamic economic theory is not only based on conventional economic principles, but is also reflected in deep Islamic ideology and theology.